Connecting the Unobserved Dots : A Decomposition Analysis of Changes in Earnings Inequality in Urban Argentina, 1980-2002 - Demombynes, Gabriel; Metzler, Johannes (World Bank, Washington, DC, 2012)
There are several possible explanations for the observed changes in inequality, the returns to education, and the gap between the wages of informal and formal salaried workers in Argentina over the period 1980-2002. Largely due to the lack of evidence for competing explanations, skill-biased technical change is the most likely explanation for the increases in the returns to education that occurred in the 1990s. Using a semi-parametric re-weighting variance decomposition technique and data from the Permanent Household Survey, the authors show that during the same period there was an increase in the returns to unobserved skill. This finding lends support to the hypothesis that skill-biased technical change has been a main driver of increases in inequality in Argentina. The pattern of changes suggests that the growth in returns to unobserved skill may have been partly responsible for the relative deterioration of informal salaried wages during the 1990s.